(untitled) (New York, 2006)
The book offers an incisive collection of contemporary research into the problems of crime control and punishment. It has three inter-related aims: to take stock of current thinking on punishment, regulation, and control in the early years of a new century and in the wake of a number of critical junctures, including 9/11, which have transformed the social, political, and cultural environment; to present a selection of the diverse epistemological and methodological frameworks which inform current research; and finally to set out some fruitful directions for the future study of punishment
Keywords: Punishment,Punishment,Criminal justice, Administration of; Europe